2008
DOI: 10.1136/ip.2008.018374
|View full text |Cite
|
Sign up to set email alerts
|

Examining the sensitivity of an injury surveillance program using population-based estimates

Abstract: This study uses population-based estimates to assess the sensitivity and representativeness of an injury surveillance system using a 1-year population-based approach. Data from the Ottawa Canadian Hospitals Injury Reporting and Prevention Program (CHIRPP) site (Children's Hospital of Eastern Ontario) were compared with those from six expansion sites. The overall sensitivity of CHIRPP was 43% of all treated injuries and 57% of injuries treated at emergency departments. CHIRPP was less likely to be representativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 7 publications
1
20
0
4
Order By: Relevance
“…Macpherson et al 2 make no mention of data use, no doubt because that is not the subject of the paper; Shipton and Stone1 tell us that local public health officials were “pleased to have the system in place”. But, to be blunt—so what?…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Macpherson et al 2 make no mention of data use, no doubt because that is not the subject of the paper; Shipton and Stone1 tell us that local public health officials were “pleased to have the system in place”. But, to be blunt—so what?…”
Section: Discussionmentioning
confidence: 99%
“…The paper by Macpherson and her colleagues2 is an elegant, well-reported study of the sensitivity and representativeness of the Canadian version of CHIRPP as it operates in Ottawa. The results suggest that both elements are disappointing, although I suspect the results might be better at other sites.…”
Section: The Ottawa Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Over two million records have been collected nationally since CHIRPP's establishment in 1990 (Mackenzie and Pless, 1999). Although not population-based, a number of studies have shown CHIRPP to be representative in some contexts (Macpherson et al, 2008;Pickett et al, 2000;Kang et al, 2013;Macarthur and Pless, 1999a,b).…”
Section: Canadian Hospitals Injury Reporting and Prevention Program (mentioning
confidence: 97%